A qualitative systematic review of umbilical cord care practices in Nigeria - Precious Ebube Anyakorah; Florence Chinelo Aguna; David Chinaecherem Innocent; Anthony Chinonso Uwandu-Uzoma; Uzochukwu Godswill Ekeleme; Chidera Chisom Obasi; Stanley Chinedu Eneh; Chidinma Peace Ahunam; Ihuoma Chimdimma Dike; Vivian Chidimma Maduekwe; Oluwaseunayo Deborah Ayando; Chinazaekpere Oguguo Duruji; et al. (BMC Pediatrics)
Abstract Background Umbilical cord care is an important aspect of newborn health, and different practices exist around the world, often influenced by cultural, healthcare infrastructure, and socioeconomic factors. The objective of this systematic review is to synthesize current literature on umbilical cord care practices in Nigeria, with an emphasis on the impact of cultural beliefs, healthcare infrastructure, and socioeconomic factors. Methods A comprehensive search for literature was performed across PubMED, MEDLINE and Google scholar for studies published between 2010 and 2023. The preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines was followed for the execution of this study. Eligibility criteria included only English studies investigating umbilical cord care practices in Nigeria, with outcomes connected to cultural, healthcare, or socioeconomic factors. Critical Appraisal Skills Programme (CASP) checklist was used to critically appraise the quality and rigor of selected studies. Due to the heterogeneity of the studies (qualitative and quantitative), qualitative narrative synthesis was used to synthesize the studies in a textual format for comprehensive understanding. Results A total of 11 included studies were found out of 1532 studies. The findings reveal a range of cord care practices, emphasizing the use of various methods such as methylated spirit, hot compresses, and indigenous substances. Cultural beliefs, a lack of healthcare infrastructure, and socioeconomic circumstances all have a big impact on cord care decisions. Disparities in knowledge and adherence to evidence-based procedures are noticeable, particularly in the use of chlorhexidine gel. Infections continue to be a problem, highlighting the significance of appropriate therapies. Conclusion This systematic review offers a comprehensive perspective of Nigerian umbilical cord care practices, emphasizing the importance of culturally responsive educational interventions, enhanced healthcare infrastructure, and targeted legislative measures. Despite its limitations, the study is an important resource for guiding future research, policy creation, and interventions to improve maternal and newborn health outcomes in Nigeria.